Penerapan Model Pembelajaran Probing Prompting Terhadap Kemampuan Pemahaman Konsep Matematika Siswa - Eka Rosdianwinata; Muhammad Ridwan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
THE IMPLEMENTATION OF PROBING PROMPTING LEARNING MODEL ON UNDERSTANDING SKILLS OF STUDENT MATHEMATICS CONCEPT. This study aims to determine the ability of understanding the Probing Prompting grade VIII MTs MA Cikaliung model. The research method used posttest-only nonequivalent control group design. Based on the results of hypothesis testing obtained t count = 0.883 and ttable = -1.672 with significance level α = 0.05. The words H0 and H1 are rejected, things that require an understanding of mathematical concepts capable of digging better than others.